FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYARAKAT DI DESA RANTAU KEMBANG KABUPATEN TEBO TAHUN 2018 – 2020 - Titik Winarsih; M. Subhan; Titin Agustin Nengsih (EKSYA : Jurnal Ekonomi Syariah, 2022)
The purpose of this study was to identify the factors that affect the welfare of the people of Rantau Kembang Desa Kab. Tebo Year 2018-2020. This type of research is quantitative using primary and secondary data sources. The population in this study came from Rantau Kembang Village, Kab. tebo. The sampling model in this study uses non-probability sampling. The results of the analysis, the financial management accountability variable shows a significance level of 0.049 which affects the welfare of the community, the significance level for village policies is 0.283. It does not affect the welfare of society. The level of significance for rural institutions is 0.450, which does not affect people's welfare. Community welfare is influenced by the accountability of financial management, village policies and village institutions with a significance level of 0.038.